MINTAQALAR INVESTITSION SALOHIYATINI SHAKLLANTIRISHNING INSTITUTSIONAL ASOSLARI (Marketing Journal, 2026)
AbstractThis article examines the institutional foundations for the formation of regionalinvestment potential. Particular attention is given to key institutional factors, includingregulatory environment, governance systems, investment infrastructure, andinvestment support mechanisms. The study identifies priority directions for improvinginstitutional conditions to enhance regional investment attractiveness and proposesscientifically grounded recommendations. The findings contribute to strengtheninginstitutional capacity and improving regional investment development.Keywords: investment potential, institutional environment, regionaldevelopment, investment attractiveness, institutional mechanisms, investmentinfrastructure.